Advanced nitrogen and phosphorus removal by the symbiosis of PAOs, DPAOs and DGAOs in a pilot-scale A2O/A+MBR process with a low C/N ratio of influent. (1st February 2023) - Li, Siqi; Guo, Yu; Zhang, Xuan; Feng, Liang; Yong, Xiaolei; Xu, Jing; Liu, Yanchen; Huang, Xia
Highlights: Advanced TN (7.0 ± 2.2 mg N/L) and TP (0.36±0.32 mg P/L) removal was obtained in the A 2 O/A+MBR process. Anoxic units contribute the most to TP removal (65.5%) by denitrifying phosphorus removal. Increasing the relative abundance of Tetrasphaera was conducive to releasing phosphorus. DPAOs and DGAOs cooperated in nitrogen and phosphorus removal processes. Dechloromonas (dominant DPAOs) played a vital role in the removal of TN and TP. Abstract: Cooperating in harmony to avoid competition with dominant functional microbial symbiosis is an efficient way in advanced nitrogen and phosphorus removal in wastewater treatment processes. In this study, a niche-based coordinating strategy was implemented to cooperate in harmony with phosphorus-accumulating organisms (PAOs), denitrifying phosphorus-accumulating organisms (DPAOs) and denitrifying glycogen-accumulating organisms (DGAOs) to advance nitrogen and phosphorus removal based on an anaerobic-anoxic-oxic-anoxic-membrane bioreactor (A 2 O/A+MBR) under low C/N in municipal wastewater influent. The niche-based strategy was conducted based on the ORP change during the process as an indicator combined with the adjustment of recirculation and anoxic zone shifting. The results indicated that the strategy of the post-anoxic unit could enable significant enhancement of biological nitrogen and phosphorus removal (BNPR) by 9.9% and 16.3%, respectively, with low effluent concentrations of 7.0 ± 2.2 mg N/L and 0.36±0.32 mg P/L. The satisfactory performance was dominated along with the shift in the microbial community: the relative abundance of Tetrasphaera (PAO genus) increased from 0.14±0.08% to 0.32±0.12%, while the relative abundance of Decchloromonas (DGAO genus) and Candidatus Competibacter (DGAO genus) also increased. The advanced combination of anaerobic phosphorus release, anoxic denitrification, denitrifying phosphorus removal and endogenous denitrification was qualified by the modeling simulation of the biochemical kinetics mechanism of activated sludge in the A 2 O+MBR and A 2 O/A+MBR processes, which means that cooperation in the harmony of PAOs, DPAOs and DGAOs could be efficiently realized by a promising control strategy to enhance BNPR in an A 2 O+MBR with a post-anoxic unit. This study provides an efficient and simple novel control strategy to overcome the limitation of traditional nitrogen and phosphorus removal under an insufficient carbon source. Graphical abstract: Image, graphical abstract